2020
DOI: 10.3390/molecules25194470
|View full text |Cite
|
Sign up to set email alerts
|

Fluorimetric and CD Recognition between Various ds-DNA/RNA Depends on a Cyanine Connectivity in Cyanine-guanidiniocarbonyl-pyrrole Conjugate

Abstract: Two novel isosteric conjugates of guanidiniocarbonyl-pyrrole and 6-bromo-TO (thiazole orange) were prepared, differing only in linker connectivity to cyanine (benzothiazole nitrogen vs. quinoline nitrogen). The quinoline analog was significantly more susceptible to aggregation in an aqueous medium, which resulted in induced circular dichroism (ICD; λ = 450–550 nm) recognition between A-T(U) and G-C basepair containing polynucleotides. The benzothiazole-isostere showed pronounced (four-fold) fluorimetric select… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Mostly, the compounds 1-6 did not show a stabilizing effect on ds-DNA and ds-RNA at ratio, r [compound]/[nucleotide phosphate] = 0.1 (Figures S27-S29 in SI). Only compound 5 with thiopropyl substituent on the N atom of the benzothiazolyl chromophore exhibited the stabilization effect on AT-DNA (∆T m value = 4 • C) [10,35,36]. Close derivative 6 with thioethyl substituent did not show any impact on DNA/RNA thermal stability.…”
Section: Study Of Interactions Of 1-6 Withmentioning
confidence: 93%
See 1 more Smart Citation
“…Mostly, the compounds 1-6 did not show a stabilizing effect on ds-DNA and ds-RNA at ratio, r [compound]/[nucleotide phosphate] = 0.1 (Figures S27-S29 in SI). Only compound 5 with thiopropyl substituent on the N atom of the benzothiazolyl chromophore exhibited the stabilization effect on AT-DNA (∆T m value = 4 • C) [10,35,36]. Close derivative 6 with thioethyl substituent did not show any impact on DNA/RNA thermal stability.…”
Section: Study Of Interactions Of 1-6 Withmentioning
confidence: 93%
“…For example, cyanine dyes with phosphonium substituents showed unusual kinetic recognition between minor grooves of homo and alternating AT-DNA sequences while guanidiniocarbonyl-pyrrole and bromo TO derivative enabled selective recognition of double-stranded (ds-) RNA vs. ds-DNA [8][9][10]. Similar discrimination between ds-DNA and ds-RNA structures was shown by oxazole yellow homodimer (YOYO), whereas chlorinated TOTO (thiazole orange homodimer) demonstrated preferential binding to alternating DNA sequences compared to non-halogenated TOTO [11].…”
Section: Introductionmentioning
confidence: 99%
“…The design of substituents in the terminal nuclei of MCDs can directly affect the interaction with biomacromolecules. In [49], two guanidiniocarbonyl-pyrrole conjugates (GCP) of MCDs were obtained (dyes 27 and 28; Figure 15), and their interaction with nucleotides was studied. The conjugates practically do not fluoresce in solution and exhibit strong fluorescence in the presence of dsRNA and dsDNA nucleotides.…”
Section: Monomeric MCDmentioning
confidence: 99%
“…New MCDs (dyes 100-103; Figure 26) were proposed as theranostic agents; the dyes showed cell growth-inhibitory effects on cancer cells (lines HCT 116; MCF-7 and H460) [21]. Screening against human lung carcinoma (A549) showed that guanidiniocarbonylpyrrole conjugates of MCDs accumulate effectively in cell mitochondria, causing moderate cytotoxic effects, which make them favorable for use in theranostics [49].…”
Section: Application Of Monomethine Cyanine Dyes In Biochemistry and ...mentioning
confidence: 99%